Analysis of the Effects of Demographic and Socioeconomic Factors on the Amount of Solid Waste Generation in Regencies and Cities in East Java During the 2019-2023 Period - Nabil, Muhammad Haidar; Sri muljaningsih (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This study aims to assess the impact of demographic and socio-economic factors on the volume of waste generated in districts/cities in East Java during the 2019-2023 period. The analysis was conducted by considering the population variable as a demographic factor, as well as the average level of education and Gross Regional Domestic Product (GRDP) per capita as socio-economic factors. Waste is one of the main challenges in environmental management, where suboptimal handling can have adverse effects on health, ecosystems, and the economy. This study aims to analyze how socio-economic and demographic factors affect the amount of solid waste generated by the community and also as a basis for the use of variables that can be used for a more effective and efficient predictive model of future waste generation. This study applies the panel data regression statistical method to evaluate the relationship between demographic and socio-economic aspects and the amount of waste, while illustrating the impact of economic activity and social conditions on the environment. The results show that population as a demographic element, as well as education level and GRDP per capita as socio-economic indicators, have a significant positive influence on the amount of waste generated by the community. The results of this study can support policy implications in encouraging new strategies to reduce waste generation and integrate environmental governance.